The Different Ways the Quran was Received in Central Java Indonesia - Misbah, Muhammad (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2023)
This article discusses the various receptions of the Al-Quran by the Javanese. The research aims to understand how the Al-Quran is received and understood in the Javanese cultural through oral reception, written reception, actions, and visual reception. The problems have a key role in disseminating Islamic teaching to all regions in Nusantara. The research methodology employed a qualitative approach with techniques such as interviews, observations, and content analysis for data collection. The findings of this research are providing valuable insights the various receptions of the Al-Quran. In the Javanese cultural, the Al-Quran is understood not only through its text but also through oral practices, writings, actions, and visuals. This understanding enriches our comprehension of the interaction between religion and culture, provides a more comprehensive depiction of the influence of the Al-Quran in the everyday lives of the Javanese community.Pelbagai Cara al-Quran Diterima di Jawa Tengah Indonesia. Artikel ini membahas berbagai resepsi al-Quran bagi orang Jawa. Penelitian ini bertujuan untuk memahami bagaimana al-Quran diterima dan dipahami dalam kerangka budaya Jawa melalui resepsi lisan, resepsi tertulis, tindakan, dan resepsi visual. Permasalahan tersebut memiliki peran kunci dalam mensosialisasikan ajaran Islam ke seluruh wilayah di Nusantara. Metodologi penelitian menggunakan pendekatan kualitatif dengan teknik pengumpulan data berupa wawancara, observasi, dan analisis isi. Temuan penelitian ini memberikan wawasan berharga tentang pelbagai resepsi al-Quran. Dalam budaya Jawa, al-Quran dipahami tidak hanya melalui teksnya tetapi juga melalui praktik lisan, tulisan, tindakan, dan visual. Pemahaman ini memperkaya pemahaman kita tentang interaksi antara agama dan budaya, memberikan gambaran yang lebih komprehensif tentang pengaruh al-Quran dalam kehidupan sehari-hari masyarakat Jawa.